Antecedents of Switching Intention of Mobile Phone Subscribers via Mobile Number Portability Service (Dhaka University Journal of Business Studies, 2023)
This study investigates the switching intention of mobile subscribers in the telecommunication industry of Bangladesh. Data were collected through an online survey with a structured questionnaire from the subscribers of different mobile operators in Bangladesh who have used the Mobile Number Portability (MNP) service. The Binary Logistic Regression Analysis was performed to test the research hypotheses. Results show that among the nine predictors, two variables, including call rate and data cost, are positively correlated with the switching intention of cellphone users in Bangladesh and contribute approximately 41 times and 109 times, respectively. However, three predictors, including internet browsing speed, network strength, and user’s gender, do not significantly affect customers' switching intention. Finally, the limitations and managerial implications of the study, along with future research avenues, have been discussed.Journal of Business Studies, Vol. XLII, No. 2, August 2021 Page 203-209